BIMG-03. MOLECULAR IMAGING OF GLUCOSE METABOLISM FOR INTRAOPERATIVE FLUORESCENCE GUIDANCE DURING GLIOMA SURGERY - Belykh, Evgenii (Neurooncol Adv, 2021)
PURPOSE: This study evaluated the utility of using molecular imaging of fluorescent glucose analog 2-(N-(7-Nitrobenz-2-oxa-1,3-diazol-4-yl)Amino)-2-Deoxyglucose (2-NBDG) as a discriminatory marker for intraoperative tumor border identification in a mouse glioma model. PROCEDURES: 2-NBDG and were assessed in GL261 and U251 orthotopic tumor bearing mice. Intraoperative fluorescence of 2-NBDG administered topical and intravenous in normal and tumor regions was assessed with operating microscope, handheld confocal laser scanning endomicroscope (CLE) and benchtop confocal laser scanning microscope (LSM). Additionally, 2-NBDG fluorescence in tumors was compared to 5-aminolevulinic acid-induced protoporphyrin IX fluorescence. RESULTS: Intravenously administered 2-NBDG was detectable in brain tumor and absent in contralateral normal brain parenchyma on wide field operating microscopy imaging. Intraoperative and benchtop CLE showed preferential 2-NBDG accumulation in the cytoplasm of glioma cells (tumor-background ratio of 2.76±0.43). Topically administered 2-NBDG did not create a sufficient tumor-background contrast for white field operating microscopy imaging, or under benchtop LSM (tumor-background ratio 1.42 ± 0.72). However, topical 2-NBDG did create sufficient contrast to evaluate cellular tissue architecture and differentiate tumor cells from normal brain parenchyma. PpIX imaging resulted in a more specific delineation of gross tumor margins than IV or topical 2-NBDG, and a significantly higher tumor-normal brain fluorescence intensity ratio. CONCLUSION: After intravenous administration, 2-NBDG selectively accumulated in the experimental brain tumors and provided bright contrast under wide field fluorescence imaging with a clinical grade operating microscope. Topical 2-NBDG was able to create a sufficient contrast to differentiate tumor from normal brain cells based on visualization of cellular architecture with CLE. 5-ALA demonstrated superior specificity in outlining tumor margins and significantly higher tumor-background contrast. Given its non-toxicity, using 2-NBDG as a topical molecular marker for noninvasive in vivo intraoperative microscopy is encouraging, and warrants further clinical evaluation.